Utilization of Water Turbidity Meter Devices in Estimating the Aggregate Stability of Many Artificially Stabilized Soils - Mutter, Ghazi Maleh (International Journal of Integrated Engineering, 2018)
This study is designed to utilize portable turbidity meters, usually available in most water analysis laboratories, in developing of a quick Dispersion Ratio test (DR, %) as an index of soil stability. The work includes: first, the use of many stabilizers (Bitumen, Lime and Cement) in the preparation of many artificially stabilized lead contaminated soil; second, the measurements of the scouring depth (SD, in mm), by a â€œMiniâ€ Jet Erosion Test and then both the critical shear stress (Ï„c, pa) and the erodibility coefficient (kd, cm3/kN.s); and finally, the comparisons between dispersion ratio (DR, %) values of soils, as estimated by a portable turbidity meter first and then by the gravimetric method. The results showed that all stabilizers can markedly improve the stability of soil; either as (SD, Ï„c, and kd) or as (DR, %) and cement was the best. In general, good correlations were found between the turbidity (NTU) and suspended solids (mg/l) of the stabilized soils (R= 0.99, 0.96 and 0.97) for bitumen, lime and cement, respectively. However, the turbidity DR (%) appears to have a higher correlation with both lime (R= -0.98) and bitumen (R= -0.96) and in a lesser extent with cement (R= -0.87); because only 3% cement could sharply reduce DR of the untreated soil from 7.03 to 2.54%, compared with 4.9 and 4.25% for lime and bitumen respectively. Moreover, the turbidity DR (%) seems to be highly correlated with the kd of soils (R= 0.99, 0.96 and 0.90) for cement, bitumen and lime, respectively and cement was a superior in the reduction of both kd and DR (%) even at 3%. The salient conclusion of this work is that the turbidity DR (%) can be easily utilized to be as a successful index of soil stability. Because this method is quick and of results that are highly correlated with the erodibility coefficient (kd), this may suggest and recommend the use of the turbidity meter devices in estimating the stability of artificially stabilized soils and other similar soils.